Next-generation direct reprogramming - Keshri, Riya; Detraux, Damien; Phal, Ashish; McCurdy, Clara; Jhajharia, Samriddhi; Chan, Tung Ching; Mathieu, Julie; Ruohola-Baker, Hannele (Frontiers in Cell and Developmental Biology, 2024)
Tissue repair is significantly compromised in the aging human body resulting in critical disease conditions (such as myocardial infarction or Alzheimer's disease) and imposing a tremendous burden on global health. Reprogramming approaches (partial or direct reprogramming) are considered fruitful in addressing this unmet medical need. However, the efficacy, cellular maturity and specific targeting are still major challenges of direct reprogramming. Here we describe novel approaches in direct reprogramming that address these challenges. Extracellular signaling pathways (Receptor tyrosine kinases, RTK) and epigenetic marks remain central in rewiring the cellular program to determine the cell fate. We propose that modern protein design technologies (AI-designed minibinders regulating RTKs, epigenetic enzymes, or pioneer factors) have potential to solve the aforementioned challenges. An efficient transdifferentiation/direct reprogramming may in the future provide molecular strategies to collectively reduce aging, fibrosis, and degenerative diseases.